Ethanol Production from Nondetoxified Dilute-Acid Lignocellulosic Hydrolysate by Cocultures of Saccharomyces cerevisiae Y5 and Pichia stipitis CBS6054. (26th June 2012) - Wan, Ping; Zhai, Dongmei; Wang, Zhen; Yang, Xiushan; Tian, Shen
Abstract : Saccharomyces cerevisiae Y5 (CGMCC no. 2660) and Issatchenkia orientalis Y4 (CGMCC no. 2159) were combined individually with Pichia stipitis CBS6054 to establish the cocultures of Y5 + CBS6054 and Y4 + CBS6054. The coculture Y5 + CBS6054 effectively metabolized furfural and HMF and converted xylose and glucose mixture to ethanol with ethanol concentration of 16.6 g/L and ethanol yield of 0.46 g ethanol/g sugar, corresponding to 91.2% of the maximal theoretical value in synthetic medium. Accordingly, the nondetoxified dilute-acid hydrolysate was used to produce ethanol by co-culture Y5 + CBS6054. The co-culture consumed glucose along with furfural and HMF completely in 12 h, and all xylose within 96 h, resulting in a final ethanol concentration of 27.4 g/L and ethanol yield of 0.43 g ethanol/g sugar, corresponding to 85.1% of the maximal theoretical value. The results indicated that the co-culture of Y5 + CBS6054 was a satisfying combination for ethanol production from non-detoxified dilute-acid lignocellulosic hydrolysates. This co-culture showed a promising prospect for industrial application.